PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI MIND MAPPING TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Farizal Firdaus; Marmi; Dina Chamidah; Sunaryo (Journal of Natural Sciences and Learning, 2022)
Motivation to learn is a feeling that occurs because of the impulse within or outside the human being to be excited about achieving a goal, as well as being a force that can influence hopes and ideals to be achieved. In this study, it was discussed about the material of the human digestive system of biology subjects that use the Problem Based Learning model associated with MindMapping to encourage students to have high motivation which will have a positive impact on achievement or learning outcomes. Differences with conventional learning models or lectures still have to be updated with problem-based learning models. Validation of this model uses a comparison between learning implementations that use experimental and control classes. Thecalculation results of this model are very significant using several inferential statistical tests. The use of this statistical test can obtain valid results. The results of the experimental class are 92.50 and the control class is 78.75.